Respostas

2013-12-28T11:39:39-02:00
Se...N=(1/5 - 2/3)² + (1/5 - 2/3)²
fazemos as contas normalmente...assim,

N=(1/5 - 2/3)² + (1/5 - 2/3)² (tira o m.m.c)
N=( \frac{3-5}{15} )² + ( \frac{3-10}{15}
N=( \frac{-2}{15} )² + ( \frac{-7}{15}
N= \frac{4}{225} + \frac{49}{225}
N= \frac{53}{225}

1 5 1
2013-12-28T12:09:29-02:00
Sendo N (1/5 - 2/3)² + (1/5 - 2/3)². Qual o resultado?
(1 - 2)²  + (1 - 2)²  =
 5   3        5   3

1º vamos calcular o que está nos parênteses:
mmc (3, 5) = 15
(3 - 10)²  + (- 10)² = 
   15            15
(- 7)²  + (- 7)² =
 15         15
 49   +   49     =  
225      225
Resposta: 
 98    
225